Effect of mulberry leaf extract (Morus nigra L.) on cardiovascular inflammatory process and insulin resistance of dyslipidemic mice (Research, Society and Development, 2022)
Objective: To evaluate the effect of mulberry leaf extract on cardiovascular inflammation, insulin resistance and left ventricular hypertrophy in dyslipidemic mice. Methodology: Knockout mice for the LDL receptor gene were divided into four experimental groups (n=20): group S (Standard), fed a standard diet; group SA (Standard / Mulberry), fed a standard diet and mulberry leaves extract; group HL (Hyperlipidic), fed a hyperlipidic diet and group HLA (Hyperlipidic / Mulberry), fed a hyperlipidic diet and mulberry leaves extract. After 15 days of experiment, plasma was collected and the plasma levels of total cholesterol and its fractions, triglycerides, C-reactive protein, insulin, glucose were quantified and the Homa index calculated. Heart and aortic wall tissues were collected to quantify the expression of CD40L by the western blotting method. Histological slides with heart tissue were prepared and stained with hematoxylin and eosin for general histological evaluation and stained with picrosírius red to evaluate the collagen deposit area. Results: Mulberry leaf extract elevated plasma HDL, moderately prevented hypercholesterolemia and did not reduce hypertriglyceridemia in HLA group mice, prevented insulin resistance and consequently hyperinsulinemia, reduced plasma CRP level and prevented increased CD40L expression. Conclusion: Treatment with mulberry leaves extract prevented cardiovascular inflammation and insulin resistance, thus reducing the development of left ventricular hypertrophy.